Investigation of Wet-Preparation Methods of Nickel Foam For Alkaline Water Electrolysis. Issue 1 (1st February 2023) - Ferriday, T.B.; Sampathkumar, S.N.; Middleton, P.H.; Van Herle, J.
Abstract: Water electrolysers are multi-component systems whose performance relies on each part performing its task. A great emphasis has been placed on the development of efficient catalyst-coated electrodes, however the efficacy of the underlying substrate itself has been overlooked. This paper investigates the resulting performance of nickel foam electrodes in 1.0 M KOH after being treated in various concentrations of hydrochloric acid and sulphuric acid. The greatest performance was achieved utilising 0.50 M H2 SO4 as measured by LSV, EIS and CV and ECSA, resulting in a 27% decline in series resistance relative to untreated nickel foam. The series resistance decreased continuously with acid concentration until a plateau was reached at the concentration of 0.5 M, where this trend was seen for both types of acid. Utilising these preparation methods for nickel foam electrodes can notably enhance electrode performance.